Fission Fragment Angular Momenta: Generation and Observation - Randrup Jørgen; Døssing Thomas; Vogt Ramona (EPJ Web of Conferences, 2024)
The fission fragment angular momenta can generally be expressed in terms of the six normal modes of rotation for the dinucleus and different models populate those modes to different degrees reflecting the mechanisms involved. For the nucleon exchange mechanism, the characteristic time scales for the various modes are discussed, leading to the expectation that the wriggling mode is fully populated, while twisting is unlikely to play a major role; bending probably has some presence which increases with mass asymmetry. Subsequently it is discussed how information about the fragment spin directions can be determined by observation of E2 emissions in even-even nuclei. It is shown how the yield ratio Y (0°)/Y (90°) in a modern Wilhelmy-type experiment can reveal the degree of twisting, a measurement that could be readily carried out now. Furthermore, with a view towards the future when the required technology has been developed, it is illustrated how the relative role of positive modes (wriggling) and negative modes (bending and twisting) can be determined by measuring the opening angle between two E2 photons whose helicities are also identified.